Medical device design innovation from concept to market - Ogrodnik, Peter J. (Elsevier/Academic Press, 2013)
Shows the essential methodologies medical designers must understand to ensure their products meet requirements. This book brings together proven design protocols and puts them in an explicit medical context, based on the authors' years of experience in academia (R&D phase) and industrial (commercialization phase) experience.